2017
DOI: 10.21303/2504-5679.2017.00339
|View full text |Cite
|
Sign up to set email alerts
|

Р. Leu72met Mutation of Ghrelin GHRL Gene in Children With Gastroesophageal Reflux Disease

Abstract: Gastroesophageal disease (GERD) is the one of most spread diseases that injures an esophagus. Taking into account the large number of factors that can cause GERD development already in child age, including genetic predisposition, it is necessary to analyze each of them in detail. Aim of this work was to analyze a frequency and possible association type of р. Leu72Met mutation of GHRL gene in children with gastroesophageal reflux disease. The analysis of clinical parameters and course of disease in the group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Our results are partly in agreement with a previous study by Russo et al [22] that reported a reduction of both the rs696217 GT genotype and the T allele in IBS-D patients, given that when we classified our patients according to IBS subtype, no statistically significant differences were observed for any of the polymorphisms tested. Our results regarding rs696217 are in agreement with the previous study on GERD by Dats-Opoka et al [23]. Regarding the rs34911341 and rs2075356 polymorphisms, no statistically significant association with IBS was observed in this present study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are partly in agreement with a previous study by Russo et al [22] that reported a reduction of both the rs696217 GT genotype and the T allele in IBS-D patients, given that when we classified our patients according to IBS subtype, no statistically significant differences were observed for any of the polymorphisms tested. Our results regarding rs696217 are in agreement with the previous study on GERD by Dats-Opoka et al [23]. Regarding the rs34911341 and rs2075356 polymorphisms, no statistically significant association with IBS was observed in this present study.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, Russo et al [22] suggested that the GT genotype and the T allele of the GHRL rs696217 polymorphism were reduced in IBS-D patients compared to healthy individuals (HC), but only a small number of IBS-D only patients and controls were tested in this study. Additionally, Dats-Opoka et al [23] supported that the rs696217 GG genotype is associated with a threefold increase in risk for GERD development in children. Therefore, since the relative information is currently limited, in the present study, we examined the association between the risk of IBS and certain GHRL gene polymorphisms in a well-characterized cohort of Greek IBS patients.…”
Section: Introductionmentioning
confidence: 97%